Humans vs, machines; motorcyclists and car drivers differ in their opinion and trust of self-drive vehicles. (January 2023) - Pammer, Kristen; Predojevic, Helena; McKerral, Angus
Highlights: Compared with people who drive cars, motorcyclists have lower trust for human drivers. Motorcyclists compared with car drivers are less negative towards self-drive cars. Motorcyclists compared with car drivers have a higher sense of trust in self-drive cars. Car drivers express more concerns and a wider range of concerns in self-driver cars. Motorcyclists are more likely than car drivers to consider their own safety when balancing the safety of self-drive cars. Motorcyclists believe that self-drive cars will recognise their personal safety, compared to human drivers. Abstract: Self-drive vehicles have the potential to revolutionise transport systems, however their adoption by mainstream users is highly dependent on a range of factors including trust. Moreover, perceptions of self-drive cars are likely to be highly dependent on the lived-experience of different road user types. Motorcyclists have high impressions of road-vulnerability and distrust for other road users. This distrust stems from the evidence that the vast number of motorcycle crashes occur as a consequence of other-driver error. We therefore hypothesised that compared with car drivers, vulnerable road users such as motorcyclists would report high levels of other-driver distrust, but high levels of trust in self-drive cars. We conducted semi-structured interviews with motorcyclists and car drivers and found that motorcyclists are indeed distrustful of other drivers but have higher levels of trust for self-drive cars compared with car drivers, while car drivers have low levels of trust for self-drive cars, but high levels of trust for other drivers. Motorcyclists were also more likely to report a perspective of trust that centred around their own personal safety on the road. This study provides valuable insights into different road user's perceptions of AVs.